Report on the 10th AIB-CEE Chapter Conference on Navigating new Realms in Uncertain Times - Amon, Adrian (Public Finance Quarterly, 2025)
The 10th-anniversary AIB-CEE Chapter conference, held at Corvinus University Budapest, brought together 121 participants from 26 countries across 17 tracks to discuss the evolving landscape of international business. Key themes in the plenaries included the re-evaluation of internationalization theories, particularly the Uppsala Model’s limitations in the digital era, and the role of multinational enterprises (MNEs) in shaping regulatory frameworks and sustainability initiatives. Discussions highlighted the growing influence of Born Global firms and digitalized business models which challenge conventional views on gradual international expansion. Industry insights, particularly from OTP Bank, emphasized the shift toward platformbased strategies, sustainability-driven financial products, and firms’ increasing role in regulatory environments. Moreover, how MNEs navigate institutional constraints, contribute to policy development, and leverage digitalization for competitive advantage was addressed. Beyond theoretical debates, the conference featured various panels, including topics of sustainability, digitalization, future readiness, and grant application in CEE countries. Featured workshops span from networking sessions, paper development, and methodological sessions.